(3EQTGO GdWGdHjf Edi eQGJH GdYdeGAs - (3YHO GdhgGH Hf CMeO Hf Ydj GdnMnfaj, fSHg Edi eMeO GHf GdMfajI, GdTYQGfj, CHh eMeO , J (B973 (3g`s
(3ChdgG (B:s
(3bGd GdTjN ai cJGH EQTGO GdWGdHjf hSeYJ TjNfG QVi Gddg JYGdi Yfg jbhd LedI GdefGRd GdJi JfRd HgG GdChdjGA s
(3BNQgG (B:s
(3GfJgi adG jNQL CMO ef GdLgd eG OGe jLgd McekG ef GdCMcGe GdeJYdbI HeYQaI Gddg JYGdi Ch TQGFYI s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdQGHYs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B180s
(3eUOQ GbJfGA GdCUd (B:s
(3ShQjG (B(9276) s
Keywords: (3GdJUha hGdBOGH GdTQYjIs